Study the effect of thermal change in some biochemical parameters in male rats infected with diabetes mellitus experimentally. - Raisan Ibrahim, Ihsan; Jasim Al-Naeely, Ahmed (Al-Qadisiyah Journal of Pure Science, 2018)
The current study aimed to knowing the effect of different temperatures degrees for different periods on some biochemical parameters on diabetes rats. Two experiments were carried out, the first is hyperthermia 80 rats (40 healthy and 40 infected) were divided into five groups( each group subdivided into: 8 health and 8 infected). First group considered as a control group exposed to normal temperature (21 ± 2) c °, the second, third , fourth group exposed to high temperature (40 ± 2) ° C and divided two groups infected and healthy for one hour, the third group: offered to degree (40 ± 2) ° C for one, tow, four hours respectively. Secondary experiment is hypothermal it was designed in same design of first experiment and temperature used was (5 ± 2) ° CThe results showed significant increase (P <0.05) in the level of glucose, cholesterol , triglycerides ,lipoproteins and GOT in healthy group and infected and in GPT in healthy group exposed to high temperature. All group showed significant increase in all infected parameter (P <0.05) compared whit healthy group in one hour period. Unless HDL which suffered from decrease. As at increased exposure to two hours, he got the same results in the previous period except significant increase (P <0.05), which happened in the level triglycerides and VLDL in the group exposed to low temperature and decrease, which happened in LDL a infected group exposed to low temperature compared with healthy group In the period of four hours the results were similar that in the period one hour except the significant decrease (P <0.05) in cholesterol and HDL and GOT in the group exposed to low temperature compared with healthy group Levels of glucose and ALP and GOT increased in healthy animals and infected in groups expose low temperature, also HDI In LDLV significantly increase in group exposed to high temperatures, there was significantly differences in levels of cholesterol and triglycerides and HDL in the group exposed to high temperature also LDLV in group exposed to low temperature. Depending on period of of exposure